Konservatisme Akuntansi dalam Era Digital dan Keberlanjutan: Suatu Studi Literatur - Rukmana, Risa; Khaeruddin, Faizah; Jauhari, Yustika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This research aims to analyze the development of literature related to accounting conservatism in the context of modern financial accounting. .The results of this study indicate that accounting conservatism, digitalization, and sustainability accounting are three important pillars of modern financial reporting. Conservatism remains relevant as a precautionary principle, digitalization serves as a transparency enhancer, and sustainability emphasizes long-term responsibility. While there is a significant research gap, integrating these three could significantly contribute to the development of accounting theory, improved reporting quality, and more accountable and sustainable business practices.